Correction to: HPV knowledge and vaccine acceptance among European adolescents and their parents: a systematic literature review - Noelia López; Maria Garcés-Sánchez; Maria Belén Panizo; Ignacio Salamanca de la Cueva; Maria Teresa Artés; Beatriz Ramos; Manuel Cotarelo (Frontiers Media S.A., 2020)
An amendment to this paper has been published and can be accessed via the original article.